Climate Change Education and the Manitoba K-12 Curriculum: A Content-Analysis - Burton, Will (Antistasis, 2025)
This study offers a deep dive into the specific learning outcomes (SLOs) for the K-12 Manitoba curriculum detailing the frequency and depth of links to the goals of climate change education (CCE). This project explicitly builds on the work of Bieler et al. (2017) and Field et al. (2023) who undertook pan-Canadian studies on curriculum documents to identify the presence of curriculum outcomes and policies from provincial governments that aligned with CCE in K-12 schools. The aim of this study is twofold: firstly, highlighting pathways for climate conscious educators to link classroom teaching to climate change; secondly, directing areas that the province of Manitoba needs to address through curriculum reform. This paper will begin with a brief introduction to Education for Sustainable Development (ESD) which currently operates as the guiding framework for including teaching and learning on the intersection of the economy, environment, and human health and well-being in Manitoba curriculum documents. ESD will then be compared and contrasted with CCE, which is advocated as a preferred framework as it is one more commensurate with the climate emergency. Results of a content analysis of specific learning outcomes in the Manitoba K-12 curriculum documents for science, social studies and physical/health education will be detailed. The discussion section outlines changes to Manitoba curriculum in order to provide support for K-12 educators to develop learning experiences for youth that are commensurate with the current and future realities of climate change.